Pogled naprej - Konečnik Kotnik, Eva (Revija za geografijo, 2013)
This article describes the perspectives of the Department of Geography at the Faculty of Arts Maribor. First, the article focuses on and describes the research perspectives which were pointed out by the present members of the Department of Geography. In the second part, study/pedagogical perspectives of studying geography in Maribor are described from the point of view of the members of the Department. To article concludes with a consideration of the obstacles and the development opportunities for the Department of Geography in Maribor.
Keywords: Filozofska fakulteta, Oddelek za geografijo; pedagogical perspectives; pedagoške perspektive; raziskovalne perspektive; research perspectives; study of geography; študij geografije